Optimalisasi Produksi Padi Menuju Ketahanan Pangan di Jawa Tengah - Putri, Fitriani Aditya (Politeknik Statistika STIS, 2023)
In an effort to maintain the achievements of the Central Java Provincial Government as a national rice barn in order to create food security, a strategy is needed to increase rice production amid a decline in rice production in Central Java. Production input factors, such as irrigation, pesticides, and seeds, are important factors that can affect rice production. This study aims to determine the effect of the use of irrigation, pesticides, and certified seeds on rice production, as well as the effect of rice production on the food security of farming households in Central Java. Based on the 2021 Integrated Agricultural Survey (SITASI) data, the estimation results using multiple linear regression show that the use of irrigation, pesticides, and certified seeds has an effect on increasing rice production in Central Java. Meanwhile, the estimation results using binomial logistic regression show that increased rice production can increase the food security of rice farming households in Central Java. Therefore, the use of irrigation, pesticides and certified seeds needs to be optimized in various districts/cities in Central Java. The hope is that with increased rice production it will be able to achieve food security for farming households in Central Java.